Financial Management, Household Resilience and Hadith Perspective: An Analysis of Maqāṣid al-Sharī'ah in Contemporary Muslim Society - Jufri, Muhammad; Handayani, Dian; Mariani, Mariani; Suyuti, Machmud; Thahir, Ilyas (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Household financial vulnerability remains a persistent challenge in contemporary Muslim societies, often resulting from limited financial literacy and marginal integration of Islamic legal and ethical frameworks into family economic practices. This study aims to examine how the integration of hadith ethics and Islamic law can strengthen household financial literacy and resilience in the context of Muslim families. Using qualitative methods, this research analyzes classical hadith sources and contemporary studies are analyzed using the theory of maqāṣid al-sharī'ah. Data was collected by means of document studies with reference to hadith books and in-depth interviews with academics, hadith experts and Islamic law. The findings indicate that hadith ethics and Islamic legal norms such as moderation (i’tidāl), financial responsibility (amanah), avoidance of excessive debt, and halal wealth management (halal income) constitute a comprehensive moral-legal framework that not only regulates financial behavior but also enhances household resilience through values-based financial socialization, ethical consumption, and long-term economic planning. These principles foster financial discipline, reduce vulnerability to economic shocks, and promote sustainable family well-being beyond merely technical financial skills. In conclusion, within the context of the maqāṣid al-sharī’ah, the ethics of hadith on household financial literacy offers a culturally and normatively grounded model for strengthening family resilience in Muslim societies. This framework contributes to interdisciplinary discourse by bridging Islamic studies, family science, and socio-economic resilience research.